Socially Responsible Investing interconnect with the Supply Chain Management in Islamic Finance Model - Adel Ahmed (International Journal of Supply Chain Management, 2019)
The concept of Islamic finance is related to Socially Responsible Investment (SRI) by many researchers in different time frames based on the similarities between Islamic finance and the concept of SRI and Supply Chain Management (SCM). SRI has been described by many authors as an investment philosophy that includes non-financial, ethical (e.g., social and environmental) objectives. This paper will shed the light on the interconnection between concepts the Socially Responsible Investment (SRI) and the Islamic Finance Model (IFM). To explain and explore the concept of SRI within Islamic Finance qualitative research technique will be used.Â The findings show that central values in IFM and SRI could be matched to optimize prospects for Islamic finance to tap the large pool of global SRI funds. Moving forward, greater interplay between these two markets should be explored. Key stakeholders on both ends, including financial experts, research centers, rating agencies, non-governmental organizations and even regulators should pursue ways to consolidate the connectivity of these markets. The Islamic finance focuses mainly on risk sharing, individualsâ€™ rights and responsibilities, property rights and the purity of contracts. Receipt and payment of interest in contracts differentiate Islamic Finance from conventional finance. The other factors such as banned on contracts involving investments in alcohol, tobacco, drugs, pornography, prostitution, gambling, armaments, animal experimentation, genetic engineering, financial exploitation makes it similar to social responsible investment SRI.